Marketing Analyses Strategy on Core Product of Banking System at PT. MPT Jakarta Pusat - Jaenudin Akhmad; Akhmal, Akhwanul; Mardikawanty, Rini; Bambang Sutrisno, Supandi; Farida, Kania (MANAGER: Journal of Management and Administration Science, 2023)
The purpose of this study is to understand and analyze how PT. MPT would apply its marketing strategy when launching its Core Banking System, particularly by using a SWOT analysis. The method of analysis that is being used is called a qualitative field study. Utilized data collection techniques include observation, wawancara, and documentation. The findings of this study support the assertion that PT. MPT uses a 5P marketing mix strategy together with accurate and reliable segmentation, targeting, and positioning. In order to promote the Core Banking System, PT. MPT uses direct marketing techniques, holds seminars, updates BPR-specific bank documents, and uses promotional media like as websites and YouTube. According to the results of the SWOT analysis conducted, PT. MPT has the capability to apply its knowledge to the current strategy and make use of its resources to reduce risks and recruit more qualified employees. Growth is a strategy that can be used based on the SWOT analysis because the highest point of the scale is located on Kuadran 1. It is anticipated that the aforementioned strategy will be able to maximize available resources in order to open up a variety of avenues so that PT. MPT can continue to grow and prosper.